2013
DOI: 10.1021/ac3025976
|View full text |Cite
|
Sign up to set email alerts
|

Open Circuit (Mixed) Potential Changes Upon Contact Between Different Inert Electrodes–Size and Kinetic Effects

Abstract: We investigate the principle of the open circuit potential (OCP) change upon a particle collision event based on mixed potential theory and confirmed by a mimic experiment in which we studied the changes in the OCP when two different electrodes (Pt and Au) are brought into contact in a solution that contains some irreversible redox couples. A micrometer-sized Au ultramicroelectrode, when connected in parallel to a Pt micro- or nanoelectrode, showed clearly measurable OCP changes whose magnitude matches well wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 12 publications
3
64
0
Order By: Relevance
“…However as discussed in ref 24, Φ ,0 and Φ ,0 may vary with the surface area of the electrodes. Many plots in the rest of the paper, including Figure 2, will be classified subject to the value of .…”
Section:  mentioning
confidence: 97%
See 1 more Smart Citation
“…However as discussed in ref 24, Φ ,0 and Φ ,0 may vary with the surface area of the electrodes. Many plots in the rest of the paper, including Figure 2, will be classified subject to the value of .…”
Section:  mentioning
confidence: 97%
“…In principle, the area dependence of the open-circuit potential can be calculated 24 or measured. Its value will depend, i.e.…”
Section: The Two Electrode Geometry Without Bipotentiostatic Controlmentioning
confidence: 99%
“…In an equilibrium system, the OCP value of the gold electrode will remain stable; however, when the oxidation products dissolve (in addition to oxygen from the air), changes in OCP of the gold electrode will occur over time. The OCP variation will be related to the kinetics of the redox processes and the concentration of the dissolved species [41][42][43].…”
Section: Stability Of the Rawmentioning
confidence: 99%
“…The difference between the treated sample and blank electrode, however, was insignificant. The variation in the x-axis was due to changes in OCP which was dependent on the electrode surface, biofilm growth, redox reaction kinetics, and the concentration of redox species at the interface [306,307]. Considering the changes after the energy inhibitor treatment in the biofilms, our results confirmed that treatment with inhibitory agents hindered the charge transfer capability of the biofilm.…”
Section: Mechanism Of Biofilm Sensingsupporting
confidence: 67%